Use of Drains in Abdominal Surgeries: Evidence-Based Evaluation of Necessity and Complications - Iwe, Damilola Patrick; Muhammad Azam; Khan, Arslan; Qureshi, Maryam Ahmad; Erik, Abneer; Khan, Nida Zaid (Indus Journal of Bioscience Research, 2025)
This paper examines reasons why surgical drains are used during abdominal surgery and the complexities associated with its use, as well as the determination of the occurrence of the most common postoperative complications and how they relate to patient demographics. A 100 sample of abdominal surgery patients was observed with the use of descriptive statistics, Chi-square tests, ANOVA to define the pattern and connections in the data. It was established that drains were predominantly used in a case of exploratory laparotomy and colectomy and such issues as delayed wound healing, infection and pain at a site of the drain were reported in a significant number of cases. chi-square analysis revealed a significant association between type of surgery and complication, ANOVA analysis revealed no demographic restrictions in terms of age, residence variances. Our findings correspond with other researches that indicate that decision-making to use drains should be duly considered in terms of the character of an operation and patient-specific characteristics These results show that there is a potential that evidence-based utilization of drains can assist patients to avoid any unnecessary risks, and recover quicker, with a patient-centered dispatch of drains. The paper will also be of high interest to the health care provider and the surgeon as this will assist them to make better decisions concerning the use of the surgical drain hence maximizing on the positive effect of the postoperative care and minimize risk of subsequent complications.